In Vivo Safety Studies With SPBN GASGAS in the Frame of Oral Vaccination of Foxes and Raccoon Dogs Against Rabies - Ortmann, Steffen; Kretzschmar, Antje; Kaiser, Christiane; Lindner, Thomas; Freuling, Conrad; Kaiser, Christian; Schuster, Peter; Mueller, Thomas; Vos, Ad (Frontiers in Veterinary Science, 2018)
In order to obtain Marketing Authorization for an oral rabies vaccine in the European Union, not only safety studies in the target species, red fox and raccoon dog, are required. Since baits are distributed unsupervised in the environment, specific safety studies in selected non-target species are compulsory. Furthermore, oral rabies vaccines are based on live, replication-competent viruses and thus distinct safety studies in the target species for such type of vaccines are also mandatory. Here, the results of these safety studies in target and selected non-target species for a 3rd generation oral rabies virus vaccine construct, SPBN GASGAS (Rabitec), are presented. The studies included the following species; red fox, raccoon dog, domestic dog, domestic cat, domestic pig, wild rodents. The following safety topics were investigated; overdose, repeated dose, dissemination, shedding, horizontal and vertical transmission. It was shown that SPBN GASGAS did not cause disease or any other adverse reaction in vaccinated animals and naïve contact animals. The vaccine did not disseminate within the host beyond the site of entry. No horizontal transmission was observed in wild rodents. In the target species, there was evidence that in a few cases horizontal transmission of vaccine virus could have occurred under these experimental conditions; most likely immediately after vaccine administration. The vaccine construct SPBN GASGAS meets therefore the latest revised minimal safety requirements as laid down in the European Pharmacopoeia.